The roles of decoding and vocabulary in Chinese reading development: Evidence from a 3‐year longitudinal study. (13th July 2020) - Yan, Mengge; Li, Yixun; Sun, Xin; Zhou, Xuelian; Hui, Yi; Li, Hong
Abstract : Backgrounds: Decoding and vocabulary are two essential abilities to reading comprehension. Investigating the roles of decoding and vocabulary in Chinese reading development can not only provide empirical evidence to enrich the current reading theories but also have implications for educational practice. Aims: To examine the developing importance of decoding and vocabulary to reading comprehension and the reciprocal relationship between decoding and vocabulary across the reading development. Sample: A total of 186 Chinese children were followed from grade 1 to grade 3 (aged 6.5 to 8.5 years). Methods: Participants' decoding, vocabulary, and reading comprehension abilities were measured once a year for three years. Hierarchical multiple regression analyses were conducted to obtain the unique contributions of decoding and vocabulary to reading comprehension in the different grades. A cross‐lagged structural equation model was used to explore the reciprocal relationship between decoding and vocabulary over the three years. Results: Decoding and vocabulary explained nearly 40% of the variance to reading comprehension across grades, and the unique contribution of decoding decreased over the grades (from 29% to 8%) while that of vocabulary increased (from 3% to 9%). Moreover, vocabulary always predicted decoding from grade 1, but decoding predicted later vocabulary only started in grade 2. Conclusions: Decoding skills are important to reading comprehension in the early learn‐to‐read grades. However, vocabulary becomes more critical for reading comprehension in later grades. Larger oral vocabularies promote the development of decoding skills, and vice versa.